2017
DOI: 10.11604/pamj.2017.28.273.12732
|View full text |Cite
|
Sign up to set email alerts
|

Is malaria over-diagnosed? A world malaria day 2017 experience by excellence and friends management care centre (EFMC) and partners, Abuja Nigeria

Abstract: Malaria remains a major cause of mortality across the world, but particularly in sub-Saharan Africa. WHO-sponsored World Malaria Day activity has helped to improve education and has contributed to a reduction in mortality globally in the past decade. However, much needs to be done still in Africa. We report on a World Malaria Day scheme in three primary Healthcare Facilities in and around the Abuja Federal Capital Territory in Nigeria in 2017. Activity included educational talks to pregnant women and nursing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…Most of the children for whom an assessment of malaria was made presented with fever (33%), and this is in keeping with the report of Oladosu et al ( 12 ), in Lagos, but in contrast with the report of Jombo et al who reported fever in only 1.8% of the children ( 10 ). However, 28.5% of the children presenting with fever tested negative for malaria which is similar to the report of Oleribe et al in Abuja ( 16 ), and this underscores the need to test every patient presenting with fever before treatment as not every fever in children is due to malaria ( 17 ).…”
Section: Discussionsupporting
confidence: 81%
“…Most of the children for whom an assessment of malaria was made presented with fever (33%), and this is in keeping with the report of Oladosu et al ( 12 ), in Lagos, but in contrast with the report of Jombo et al who reported fever in only 1.8% of the children ( 10 ). However, 28.5% of the children presenting with fever tested negative for malaria which is similar to the report of Oleribe et al in Abuja ( 16 ), and this underscores the need to test every patient presenting with fever before treatment as not every fever in children is due to malaria ( 17 ).…”
Section: Discussionsupporting
confidence: 81%